Silver Nanoparticles: Biosynthesis Using an ATCC Reference Strain of Pseudomonas aeruginosa and Activity as Broad Spectrum Clinical Antibacterial Agents - Melisa A. Quinteros; Ivana M. Aiassa Martínez; Pablo R. Dalmasso; Paulina L. Páez (International Journal of Biomaterials)
Currently, the biosynthesis of silver-based nanomaterials attracts enormous attention owing to the documented antimicrobial properties of these ones. This study reports the extracellular biosynthesis of silver nanoparticles (Ag-NPs) using a Pseudomonas aeruginosa strain from a reference culture collection. A greenish culture supernatant of P. aeruginosa incubated at 37°C with a silver nitrate solution for 24 h changed to a yellowish brown color, indicating the formation of Ag-NPs, which was confirmed by UV-vis spectroscopy, transmission electron microscopy, and X-ray diffraction. TEM analysis showed spherical and pseudospherical nanoparticles with a distributed size mainly between 25 and 45 nm, and the XRD pattern revealed the crystalline nature of Ag-NPs. Also it provides an evaluation of the antimicrobial activity of the biosynthesized Ag-NPs against human pathogenic and opportunistic microorganisms, namely, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Proteus mirabilis, Acinetobacter baumannii, Escherichia coli, P. aeruginosa, and Klebsiella pneumonia. Ag-NPs were found to be bioactive at picomolar concentration levels showing bactericidal effects against both Gram-positive and Gram-negative bacterial strains. This work demonstrates the first helpful use of biosynthesized Ag-NPs as broad spectrum bactericidal agents for clinical strains of pathogenic multidrug-resistant bacteria such as methicillin-resistant S. aureus, A. baumannii, and E. coli. In addition, these Ag-NPs showed negligible cytotoxic effect in human neutrophils suggesting low toxicity to the host.